2018
DOI: 10.3917/sta.122.0045
|View full text |Cite
|
Sign up to set email alerts
|

L’intégration du plein air en enseignement de l’éducation physique et à la santé : trois études de cas

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…These include the lack of teacher confidence and expertise (Barfod, 2018;Barfod & Daugbjerg, 2018;Edwards-Jones et al, 2018;Higgins et al, 2006), the lack of time to prepare and conduct activities (Edwards-Jones et al, 2018), the lack of support for outdoor learning (Ruether, 2018), the lack of access to outdoor sites (Higgins et al, 2006), and weather conditions (Ruether, 2018). In Quebec specifically, studies support these observations (Maziade et al, 2018; Sport et loisir de l'Île de Montréal, 2019).…”
Section: Limiting Factors Of Outdoor Learning Integrationmentioning
confidence: 85%
See 4 more Smart Citations
“…These include the lack of teacher confidence and expertise (Barfod, 2018;Barfod & Daugbjerg, 2018;Edwards-Jones et al, 2018;Higgins et al, 2006), the lack of time to prepare and conduct activities (Edwards-Jones et al, 2018), the lack of support for outdoor learning (Ruether, 2018), the lack of access to outdoor sites (Higgins et al, 2006), and weather conditions (Ruether, 2018). In Quebec specifically, studies support these observations (Maziade et al, 2018; Sport et loisir de l'Île de Montréal, 2019).…”
Section: Limiting Factors Of Outdoor Learning Integrationmentioning
confidence: 85%
“…This study identified factors that facilitate the use of the outdoors in preschool and primary settings that had already been identified by the literature, such as 1) support from the educational community for outdoor integration (school team/management/community) (Maziade et al, 2018) and 2) material and financial support (Maziade et al, 2018; Sport et loisir de l'Île de Montréal, 2019). New factors that would facilitate the use of the outdoors in preschool and primary settings also emerged from this research.…”
Section: Doi: 20mentioning
confidence: 99%
See 3 more Smart Citations